Assessment Of The Oral Cavity In Children With Congenital And Acquired Heart Defects (Eurasian Medical Research Periodical, 2024)
It is based on the correlation between clinical functional, biochemical and cytological indicators in the body and clinical symptoms of the main dental diseases in the oral cavity in children with common heart disease. In children diagnosed with a common heart defect, biophysical changes in oral fluid parameters, level of hygiene in the oral cavity, and inflammatory reaction in the periodontal soft tissues were found to be the main risk factors for the development of dental caries. High preventive efficiency of remineralizing therapy with deep fluoridation has been found. The positive effect of controlled tooth brushing, adherence to oral hygiene, selection of hygiene products, and quarterly visits to the dentist's office, which are part of the complex of treatment and prevention of dental diseases in children with common heart defects, have been proven.